EFFECTS OF DEHYDROEPIANDROSTERONE SULFATE UPON PHENOTYPE AND IN VITRO FUNCTIONS OF DENDRITIC CELLS - N. V. Seledzova; N. A. Khonina; M. A. Tikhonova; A. A. Ostanin; N. M. Passman; E. R. Chernykh (Медицинская иммунология)
Abstract. The study deals with evaluation of dehydroepiandrosterone sulfate (DHEAS) effects upon phenotype and functions of dendritic cells (DCs), generated from blood monocytes of pregnant women by means of GM-CSF and IFN-alpha. It was shown, that initial supplementation with DHEAS (10-6 M, day 1 of culture) did not influence the pattern of DC subsets. Meanwhile, addition of DHEAS at the stage of DC maturation (last day of culture) is accompanied by a significant increase in mature CD83+ cells and activated DCs (CD25+), like as their precursors (CD1a+). Furthermore, the DCs generated in presence of DHEAS were characterized by marked allostimulating activity and decreased ability to downregulate the numbers of CD56+CD16+ NK cells. Hence, DHEAS promotes generation, maturation, and allostimulating activity of DCs, along with decreased negative regulation towards CD56+CD16+NK cell amounts. DHEAS-mediated changes in DCs’ phenotype and functioning are discussed as a possible mechanism of disturbed immunological tolerance to fetal antigens in pregnant women with suprarenal hyperandrogenia.